Studi Sistem Drainase Kali Tutup Barat Kabupaten Gresik Berbasis Konservasi Untuk Penanganan Genangan - Ubaidillah, Ubaidillah; Bisri, M.; Ismoyo, M. Janu (Fakultas Teknik, Universitas Brawijaya, 2012)
Gresik city growth, accompanied by the increase of population, urbanization and industrial development poses a considerable impact on the hydrological cycle and reduces the absorption region, resulting in flooding. Floodprone area is around market of the city. The issues raised in the field can be analyzed and poses conditions of the existing drainage system of Kali Tutup Barat Gresik as well as the handling based conservation using Bozem and injection wells. The study results found that the drainage system of Kali Tutup Barat Gresik is unable to cope with puddle. Of the available land, the bozem capacity can accommodate puddle discharge of 4.444 m3, while the injection wells at 706,5 m3.Key words: Population density, drainage, bozem, injection wells